Hambatan Guru dalam Pelaksanaan Pembelajaran Tematik di MIN 11 Aceh Barat - Rahmi, Rina; Adila, Monica; Sari, Rosi Novita; Armanusa, Sri (rogram Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Thematic learning is theme-based learning that relates some of the content of subjects so that it can provide meaningful experiences to students. Since it was first implemented in 2013, integrated thematic learning has generated a lot of controversy and complaints from teachers from various regions in Indonesia about the difficulty of implementing such learning. The purpose of this study about the barriers in thematic learning in MIN 11 West Aceh. This research is a type of descriptive qualitative research. The data needed in this study were collected through observation, interview, and documentation methods. While the data analysis techniques use policy research. Based on the results of research conducted, it is known that the obstacles experienced by teachers are: 1) do not understand the concept of thematic learning; 2) difficulty relating the theme of the content of the lesson to the other content; 3) difficulty in preparing thematic lesson plans; 4) thematic evaluation; in this case, the teacher only focuses on cognitive aspects, while affective and psychomotor.